2017
DOI: 10.1093/jpepsy/jsx132
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Nurses Working With Youth With Chronic Pain: A Pilot Intervention

Abstract: Our single-session tailored group treatment was feasible and acceptable, and pilot data suggest that it is beneficial, but a more comprehensive approach is encouraged to reduce burnout that might be related to multiple individual, unit, and system factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…There were 7 studies that used online or web-based presentation of their programs, while 34 studies used in-person group sessions. Program durations ranged from a single 90 minute group session [88] or one-day workshop or equivalent (i.e., less than 8 hours) (n = 6) to 4-or 5-day workshops or retreats [35,36,40,87]. Multiple training sessions were distributed over a minimum of two days [79] and a maximum of 9 months [90], which included 15 weeks of mental health programming within nine months of recommended physical exercise.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There were 7 studies that used online or web-based presentation of their programs, while 34 studies used in-person group sessions. Program durations ranged from a single 90 minute group session [88] or one-day workshop or equivalent (i.e., less than 8 hours) (n = 6) to 4-or 5-day workshops or retreats [35,36,40,87]. Multiple training sessions were distributed over a minimum of two days [79] and a maximum of 9 months [90], which included 15 weeks of mental health programming within nine months of recommended physical exercise.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…While Morrison Wylde et al [70] found a marginal improvement in pediatric nurse burnout with smartphonebased intervention vs. traditional mindfulness interventions, studies investigating mindfulness interventions in other healthcare populations reported mixed results [144][145][146][147]. Similar to pediatric nurses [84], social workers showed a significant decrease in burnout after attending skills development courses [148] suggesting that improving clinical knowledge and skills may reduce burnout. This is supported by the finding that pediatric nurses with lower clinical competency and education level have increased burnout [57,90].…”
Section: Interventionsmentioning
confidence: 99%
“…7,8 Various interventions have been developed to try and reduce workplace stress for nurses. Some, such as Group Clinical Supervision (GCS), draw on social support as a resource, 9 however most research into GCS has focused on the impact of the intervention rather than group dynamics and processes.…”
Section: Introductionmentioning
confidence: 99%